El aprendizaje de las competencias matemáticas del bloque 1 “Álgebra y Funciones” estudiantes del sexto grado, Escuela Dr. Edison Calle Loaiza, Loja 2024-2025 - Castro Torres, Sandra Vanessa (2025)
This research work deals with: Learning the mathematical competencies of block 1 "Algebra and Functions" in sixth grade students, Dr. Edison School, Loaiza Street, Loja 2024-2025; for which the following general objective was planned: Contribute to the improvement of learning of block 1 "Algebra and Functions" to develop competencies in sixth grade students of the Dr. Edison School, Loaiza Street.; Likewise, in the theoretical framework, different authors were taken as a reference who helped to better understand the knowledge within the proposed research topic; We worked with the descriptive, analytical, deductive, and bibliographic methods, each of which helped to elucidate the different sections of the research work, the research was of a mixed type with a descriptive approach; the population investigated includes one teacher and 22 students; for which a survey and an interview with the teacher were applied. It was determined that through the alternative guidelines it would significantly help students to improve the learning of the mathematical competencies of block 1 algebra and functions. In conclusion, the teacher to teach this block must apply interactive workshops using the different technological tools such as GeoGebra, Prezi, Canva in order for students to have greater confidence in the development of their learning in the different topics that the Curricular Reform makes known to us